Psychology and the historical power–body conjunction: Foucault's different view of the history and philosophy of psychology. (June 2016) - Joranger, Line
By changing his primary concepts—abstraction, alienation, dream, morale, and power—Foucault changed his perception of mental illness and the history and philosophy of psychology throughout his career. Nevertheless, despite conceptual changes, it seems that Nietzsche's genealogical view of knowledge and the historical power–body conjunction runs like a red thread through Foucault's works as early as 1961. This article highlights Foucault's coherent and divergent views on the history and philosophy of psychology and their effects on his theories, findings, and contributions.